Typology of Kurdistani Style Mosques in Iran - Ebrahim Zarei, Mohammad (Journal of Architectural/Planning Research and Studies (JARS), 2018)
Kurdistan province has been an important part of pre-Islamic Iran territory; after Islam, it changed to Jabal and Kurdistan. This region was the major part of the Ardalan state in the Safavid and Qajar periods which in newly formed political divisions are divided among several provinces including Kermanshah, Hamadan, and western Azerbaijan. Based on specific characteristics of the region a distinctive type of mosque has been established including wooden colonnaded iwan, lateral corridors, theologian’s room, yard, and entrance. These mosques are consisted of flat ceiling and colonnaded iwan / porticos which are deeply influenced by the northwestern and western regions’ architectural / building style; one of these stylistic characteristics is the plan with iwans on four corners of Shabestan. Some of these mosques are mono-iwan and some bi-iwan but all in a rather different style from the other mosques of Iran. Iwans in these mosques are built in two floors or built with wooden columns, which endorse a distinctive type which are called Kurdistani mosques in this article.